The Effect of Benson Relaxation On Pain in Post Major Surgery Patients - Alivia Mona Kaparang; Angela Vira Manengkey; Apriliane Akiko Damar; Lani Natalia Watania; Catharina Guinda Diannita (Malahayati Nursing Journal, 2022)
ABSTRACT In the United States 80% of postoperative patients experience pain but only 30-50% receive effective treatment. Effective postoperative pain management requires other therapy than pharmacology with minimal side effects such as Benson relaxation. Benson relaxation is a deep breathing relaxation method involving belief factors that are effective in reducing postoperative pain To determine the effect of Benson's relaxation on pain in post-major surgery patients. This literature review uses the thematic analysis method: a simplified approach with publications for 2012-2022 using databases: Google Scholar, MEDLINE, JSTOR. The selection of articles used a modified PRISMA flow diagram. Analysis of article eligibility uses JBI Critical appraisal Checklist tools for RCT and Quasi-Experiment. The findings of 11 articles showed that Benson relaxation combined with pharmacological therapy was proven to be effective in reducing post-major surgery pain in terms of the time of administration, procedure, and mechanism. Benson relaxation also has other benefits such as controlling physical and psychological stress. Benson relaxation has been shown to have an effect on reducing pain in post-major surgery patients. Thus, Benson relaxation can be used as an option for independent non- pharmacological interventions in the management of post-major surgery pain. Keywords : Benson relaxation, Post major surgery, Pain  ABSTRAK Nyeri pasca bedah dirasakan oleh 80% pasien di Amerika, akan tetapi  perawatan nyeri yang efektif hanya terjadi sekitar 30-50%. Manajemen nyeri pasca bedah yang efektif membutuhkan terapi selain farmakologi dengan efek samping minimal seperti relaksasi benson. Relaksasi benson adalah metode relaksasi nafas dalam dengan melibatkan faktor keyakinan yang efektif mengurangi nyeri pada pasien pasca bedah Untuk mengetahui pengaruh relaksasi benson terhadap nyeri pada pasien pasca bedah mayor. Kajian literatur ini menggunakan thematic analysis method: a simplified approach dengan publikasi tahun 2012-2022  menggunakan databases: Google Scholar, MEDLINE, JSTOR. Analisis artikel menggunakan modifikasi flow diagram PRISMA. Kelayakan artikel diuji dengan JBI Critical appraisal Checklist tools for RCT and Quasi-Experiment. Temuan kajian literatur dari 11 artikel menunjukkan relaksasi benson yang dikombinasikan dengan terapi farmakologi terbukti efektif dalam menurunkan nyeri pada pasien pasca bedah mayor ditinjau dari waktu pemberian, prosedur dan mekanisme. Relaksasi benson juga memiliki manfaat lain seperti mengontrol stres fisik dan juga psikologi. Relaksasi benson telah terbukti memberi pengaruh terhadap penurunan nyeri pasien pasca bedah mayor. Sehingga, relaksasi benson dapat dijadikan salah satu pilihan intervensi mandiri non-farmakologi dalam penanganan nyeri pasca bedah mayor Kata kunci: Relaksasi Benson, Pasca Bedah Mayor, Nyeri